Investigating the scope of criminal law in the fight against natural resources crimes in Iran and its compliance with the goals of sustainable development (SDG17) - Hossein Noroozi; Mohammad reza Parvin; Mansoor Poornoori (تحقيقات جغرافيايی, 2020)
"This article has no abstract"